Use of basil leaf ethanol extract in alginate base edible film. Issue 1 (June 2021) - Giyatmi, Giyatmi; Irianto, Hari Eko; Anggoro, Bintang; Nurhayati,; Fransiska, Dina
Abstract: Alginate is usually obtained by extracting from brown seaweed, mainly Sargassum sp which grows almost along the coasts of the islands in Indonesia. One of the efforts to utilize alginate was by employing as raw material in the production of edible film. The disadvantage of films made from carbohydrates is that they are not very good at regulating water vapor migration. One way to improve performance of edible film in inhibiting water vapor transmission is to add vegetable oil. In this study, the effect of adding basil leaf ethanol extract was observed to improve the performance of alginate-based edible film. Basil leaf extract was added at concentrations of 0.5%, 1% and 1.5%. The resulting edible films were observed for chemical characteristics (moisture content), physical characteristics (thickness, tensile strength, water vapor transmission rate, elongation, brightness, solubility) and antibacterial performance. The results showed that the concentration of basil leaf extract had a significant effect on moisture content, thickness, tensile strength, water vapor transmission rate (WVTR), and elongation values. Edible films do not have antibacterial activity against Staphylococcus aureus and Escherichia coli. The addition of basil leaf extract at a higher concentration resulted in an alginate-based edible film with lower moisture content, higher water solubility, higher thickness, higher tensile strength, lower WVTR, and lower elongation percentage.